Metabolic patterns predispose human pluripotent stem cells to spatial organization of cell fate - Deng, Chunhao; Zhang, Zhaoying; Xiao, Xia; Godoy-Parejo, Carlos; Xu, Faxiang; Song, Chengcheng; Lin, Huanyi; Li, Qinru; Fang, Shicai; Liu, Weiwei; Chen, Guokai (Frontiers in Cell and Developmental Biology, 2026)
IntroductionDuring embryogenesis, specific morphogen gradients are essential for inducing tissue pattern formation. In two-dimensional (2D) human pluripotent stem cell (hPSC) culture, distinct patterns can emerge in hPSC colonies without external morphogen gradients, implying that critical intrinsic factors may induce spatial organization. However, studying the mechanism is challenging due to the lack of efficient spatial labels.MethodsWe employed the mitochondrial membrane potential (MMP) probe JC-1 to stain and track cells within hPSC colonies. Using this tool, we assessed metabolic patterns under different culture coatings and manipulated pathways using mTOR and ROCK inhibitors.ResultsWe identified JC-1 as a durable spatial tracker, revealing a clear metabolic pattern in hPSC colonies, significantly influenced by coating materials (integrin-stimulating matrices vs. E-cadherin). This metabolic pattern correlated with spatial mesodermal cell fate under BMP4 induction. Modulation of the mTOR pathway altered the metabolic pattern and subsequent mesoderm induction.ConclusionThis study reveals that intrinsic metabolic patterns predispose hPSCs to spatial organization of cell fate and highlights JC-1 as a potent spatial marker for studying tissue patterning mechanisms.